Gestión de cobranza y su incidencia en la cartera de crédito en la cooperativa de ahorro y crédito Coorcotopaxi Ltda agencia La Maná, año 2021. - Reina Rivera, Milena Guadalupe (2022)
This research entitled "Collection management and its impact on the credit portfolio in the Coorcotopaxi ltda agency La Maná savings and credit cooperative, year 2021", has as its general objective: Analyze the collection management and its impact on the credit portfolio. credit of the Cooperativa de Ahorro y Crédito Coorcotopaxi Ltda., period 2021, in order to find the causes of the problem it faces in terms of the processes followed by the cooperative to collect the credits granted. Once the causes are known, possible solutions can be established. In this context, the following problem has been raised: ¿How do the collection management processes influence the credit briefcase of the Cooperativa de Ahorro y Crédito Coorcotopaxi Ltda.? The design used in this research is based on a non-experimental design, with a qualitative and quantitative approach. To obtain information on the current state of portfolio recovery management, descriptive and analytical methods were used and research techniques such as interviews and surveys were used, which were applied to the staff of the COORCOTOPAXI Cooperative of the La Maná Agency, this to determine the existing incidence of collection management that is currently being applied. Based on the results obtained, the proposal to develop a collection management manual was established, with the purpose of carrying out specific activities within the credit area of the Cooperative where policies, strategies, procedures are specified to carry out collection activities. card recovery effectively and efficiently.